Políticas De Igualdade Racial Nos Cadernos De Orientação Do Programa Nacional De Inclusão De Jovens (Projovem - Adolescente) Em Itapevi De 2012a 2014 - Macedo, Guilherme Bispo [UNIFESP] (2018)
This Research Investigates The Axes Of Approximation Between The Education Of Racial Relations And The System Of Socioeducation In Brazil. It Is Studied In Detail How The National Guidelines For The Education Of Ethnic-Racial Relations And Laws 10.639 / 03 And 11.645 / 08, Which Provide For The Obligation To Teach Afro-Brazilian And Indigenous History And Culture In In The National Social Assistance Plan (Pnas) And The Single Social Assistance System (Suas). More Precisely, It Seeks To Analyze The Impacts Of Racial Equality Policies In The National Youth Inclusion Program (Projovem-Adolescente). From The Theoretical-Methodological Framework Launched By Nilma Lino Gomes, It Is Shown That Among The Paths Opened By The Struggle Of The Black Movement And Law 10.639 / 03 Are The Guidelines For The Work Of Educators Who Work In The Reference Centers Of The (Cras), That Is, The Demands And Themes Of The Black Movement That Materialized In The Form Of Educational Policy From 2003, Directly Influenced The Pedagogical